Options for Results Monitoring and Evaluation for Resilience Building Operations - Williams, Anna (World Bank, Washington, DC, 2016)
Across the world, donors and a broad array of stakeholders are seeking to understand whether climate change adaptation, disaster risk management, and other resilience interventions are working, and what lessons from early implementation of investments can be shared to inform the field and improve results over time. Monitoring and Evaluation (M&E) can play an important role in achieving these objectives toward learning, accountability, and improved impact. This paper synthesizes recent work on climate and disaster resilience M&E to help identify emerging lessons from early applications and to define the key steps to develop a M&E system for climate and disaster resilience-building operations, particularly at the project level. Another objective of this paper is to support dialogue among a broader group of M&E experts and resilience project managers and implementers to further advance the design, implementation, and utility of climate and disaster resilience M&E. The paper explains overarching objectives and components for climate and disaster resilience M&E, including the common M&E objectives of learning and accountability, and four primary M&E components: principles, results frameworks, indicators, and evaluation.It is an illustrative overview of climate and disaster resilience M&E work being undertaken within and beyond the WB. Described are examples of M&E systems, other resilience and related M&E work at the WB, and broader efforts to build capacity for climate and disaster resilience M&E.